Effectiveness of Solution Focus Brief Counseling (SFBC) for Psychological Well-being of Adolescent Girls in Toxic Relationships - Zahro, Aminatuz; Ariyati, Ika; Hendar, Kus; Maba, Aprezo Pardodi (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2025)
Adolescent psychological well-being is vulnerable to disruption due to toxic relationships that can lead to stress, anxiety, and social isolation (introduction). This study aims to explore the dynamics of toxic relationships among adolescents and seeks to enhance psychological well-being by evaluating the SFBC approach as its method Using a quasi-experimental design, this study involved 24 respondents selected through purposive sampling. Measurements were conducted using the Toxic Relationship Scale, which demonstrated validity scores ranging from 0.40 to 0.79 and reliability of 0.934, as well as the Psychological Well-Being Scale, with validity scores ranging from 0.6 to 0.95 and reliability of 0.543 and 0.828. The study employed a pretest-posttest design. In the basic assumption test, the pretest and posttest results indicated that all data were normally distributed and homogeneous, with a significance value of <0.05, allowing for the use of a T-test to analyze score differences. The T-test results indicate that SFBC counseling significantly improves the psychological well-being of adolescents in the experimental group, with their scores increasing from 44.00 to 100.67. This increase is higher than that of the control group, which only rose from 44.25 to 59.25. Thus, SFBC counseling has proven effective in enhancing the psychological well-being of adolescents trapped in toxic relationships. The conclusion of this study emphasizes that Solution-Focused Brief Counseling (SFBC) can be an efficient and practical approach because it focuses on quickly applicable solutions, which aligns with the characteristics of teenagers who prefer counseling methods that provide immediate results.